(untitled) (Plant Tissue Culture and Biotechnology, 2008)
The GATEWAYTM Binary Destination Vector pH7WG2 is available for easy insertion of genes for transformation into plants. The gene of interest integrates downstream of the Cauliflower Mosaic Virus Promoter CaMV 35S by recombination. The CaMV 35S promoter is however not suitable for transformation and expression of genes in monocots like rice. We isolated and cloned a 1100 bp upstream region from two rice (Pokkali and IR64) Na/H antiporter genes into the GATEWAYTM promoter cloning vector pHGWFS7. The Pokkali promoter expressed the Ã¢-glucuronidase or GUS gene 25-fold more efficiently than the CaMV 35S promoter in rice calli, while that of IR64 was 7-fold more. The IR64 promoter however showed efficient expression in transgenic rice leaves. The promoter from Pokkali Na/H antiporter was used to replace the CaMV 35S sequence in pH7WG2. The CaMV 35S region was cut out and the linear vector fragment blunted and T-tailed. After amplification of the promoter from Pokkali rice DNA, it was A-tailed and ligated to the modified T-vector. The resultant vector, named pH7WG3, following the nomenclature at the gateway site, www.plantgenetics.rug.ac.be/gateway, can now be used for recombination of any genes for efficient rice transformation. Key words: Recombination, Binary vector, Promoter, Transformation, Rice DOI = 10.3329/ptcb.v17i1.1120 Plant Tissue Cult. & Biotech. 17(1): 47-58, 2007 (June)